Factors influencing quality of life in African-American dementia dyads. (3rd April 2021) - Bonds, Kalisha; Whitlatch, Carol J.; Song, MinKyoung; Lyons, Karen S.
Abstract: Objective: Both caregivers and the older adults they care for can experience declines in quality of life (QOL) over the course of the dementia trajectory. Little research has examined QOL in African-American caregivers and even less in African-American persons with dementia (PWDs), making it difficult to identify associated factors. Method: Guided by the Negro Family as a Social System framework, a secondary data analysis was used to examine the influence of family structure, instrumental and expressive role functions on QOL in a sample of 62 African-American dementia dyads (i.e. African-American PWDs and their African-American caregivers). Dyadic data were analyzed using multilevel modeling to control for the interdependent nature of the data. Results: On average, African-American PWDs reported significantly worse QOL than African-American caregivers. Within African-American dementia dyads, QOL covaried. African-American PWDs experienced significantly worse QOL when their caregiver was a non-spouse and they themselves perceived less involvement in decision-making. In addition, African-American caregivers experienced significantly worse QOL when they reported greater dyadic strain with the African-American PWD and were non-spouses of African-American PWDs. Conclusion: Findings suggest understanding the interpersonal characteristics (e.g., dyadic relationship, family structure and role functions) of dyads may hold promise for improving their QOL.